Summaries of Judgments, Advisory Opinions and Orders of the International Court of Justice 2018-2022 - United Nations Office of Legal Affairs (United Nations, 2023)
This publication contains summaries of the judgments, advisory opinions and orders of a substantive nature issued by the International Court of Justice, the principal judicial organ of the United Nations, from 1 January 2018 to 31 December 2022. It is the continuation of six earlier volumes on the same subject (ST/LEG/SER.F/1 and Addenda 1, 2, 3, 5 and 6), which covered the periods 1948–1991, 1992–1996, 1997–2002, 2003–2007, 2008–2012 and 2013-2017, respectively. During the period covered by this publication, the Court issued 29 judgments, advisory opinions and orders of a substantive nature. It should be noted that the materials contained herein are summaries prepared by the Registry of the Court, which do not involve the responsibilities of the Court itself.